Home Away From Home: Native American Students' Sense of Belonging During Their First Year in College. (3rd September 2017) - Tachine, Amanda R.; Cabrera, Nolan L.; Yellow Bird, Eliza
ABSTRACT: Native American students are an underrepresented population in higher education with discouraging low 1st-year persistence rates when compared with the general population. Using the peoplehood model, this analysis employed the Indigenous methodology sharing circles to explore Native American students' sense of belonging ( n  = 24) and factors that influence it during their critical 1st year in college at Southwest University (pseudonym). Findings indicated that many Native students experienced racial microaggressions and structured disconnections from their home communities. Family and the Native student center on campus provided a "home away from home" environment. Although these were important in helping students create a localized sense of belonging, they only were necessary to the extent that the culture of the institution served to invalidate the Native students' peoplehood. To support Native students' sense of belonging, institutions must validate and incorporate Native culture and perspectives within the ingrained Eurocentric cultures of non-Native colleges and universities.